Tax avoidance, capital structure, and firm value: The moderating role of profitability in LQ45 companies post-pandemic - Purnamasari, Atika; Sari, Petty Aprilia; Husin, Husin; Goenawan, Yohanes August (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
This study analyzes the effect of tax avoidance and capital structure on firm value with profitability as a moderating variable in 19 LQ45 companies during 2020-2024. It aims to address the post-pandemic literature gap by examining the moderating role of profitability. This quantitative research employs purposive sampling and panel data regression using the Random Effect Model (REM). The analysis includes heteroscedasticity, multicollinearity, t-test, Moderated Regression Analysis (MRA), and coefficient of determination (R²). The results indicate that tax avoidance positively affects firm value, while capital structure has a negative effect. Profitability does not moderate the relationship between tax avoidance and firm value, but it weakens the effect of capital structure on firm value. These findings suggest that investors respond more to tax efficiency and profitability performance, whereas high leverage is perceived as increasing risk and reducing firm value. Therefore, maintaining an optimal capital structure is essential to enhance firm value.